Performance analysis of turbocharger effect on engine in local cars - Rajoo, Srithar; Mohd. Noor, Alias; Abdul Aziz, Azhar (Universiti Teknologi Malaysia, 2003)
The performance of a gasoline-fueled internal combustion engines can be increased with the use of a turbocharger. However, the amount of performance increment for a particular engine should be studied so that the advantages and drawbacks of turbocharging will be clarified. This study is mainly concerned on the suitable turbocharger unit selection, engine conversions required and guidelines for testing a Proton 4G92 SOHC 1.6-litre naturally aspirated gasoline engine. The engine is tested under its stock naturally aspirated condition and after been converted to turbocharged condition. The effect of inter cooled turbocharged condition is also been tested. Boost pressure is the main parameter in comparing the performance in different conditions as it influences the engine torque, power, efficiency and exhaust emissions. The use of a turbocharger on this test engine has clearly increased its performance compared to its stock naturally aspirated form. The incorporation of an intercooler to the turbocharger system increases the performance even further. With the worldwide effort towards environmental-friendly engines and fossil fuel shortage, the turbocharger can help to create engines with enhanced performance,minimum exhaust emissions and maximum fuel economy.